Selective Cross‐Coupling of Unsaturated Substrates on AlI. Issue 18 (1st March 2021) - Dmitrienko, Anton; Pilkington, Melanie; Nikonov, Georgii I.
Abstract: The Al I compound NacNacAl (1, NacNac = [ArNC(Me)CHC(Me)NAr] −, Ar = 2, 6‐ i Pr2 C6 H3 ) serves as a template for the chemoselective coupling between carbonyls (benzophenone, fenchone, isophorone, p ‐tolyl benzoate, N, N ‐dimethylbenzamide, (1‐phenylethylidene)aniline) and pyridine. With the CH‐acidic ketone (1 R )‐(+) camphor, the reaction affords a hydrido alkoxide compound of Al, formed as the result of enolization, whereas an enolizable imine, (1‐phenylethylidene)aniline, and the bulky ketone isophorone, still chemoselectively couple with pyridine. In contrast, reaction with the ester p ‐tolyl benzoate results in cleavage of the ester bond together with replacement of the alkoxy group by a hydrogen atom of the pyridine moiety. This study demonstrates that for carbonyl substrates featuring phenyl substituents, the reaction proceeds via intermediate formation of η 2 (C, X)‐coordinated (X = O, N) carbonyl adducts, whereas the reaction of 1 with ( R )‐(−)‐fenchone in the absence of pyridine leads to CH activation in the pendant isopropyl group of the Ar substituent of the NacNac ligand. Abstract : Al I compound NacNacAl mediates chemoselective cross‐coupling of carbonyl substrates (non‐enolizable ketones, imines, and esters) with pyridine.